Analysis of the influence of entreprenuership behavior and services business actors on consumer satisfaction at gunung sibayak store Medan - Angelika Florencia; Ferry Hidayat (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of entrepreneurial behavior and services on business actors on consumer satisfaction at Gunung Sibayak Stores, Medan. The sample used was 70 consumers of the Gunung Sibayak Store in Medan who made repeated purchases. Data collection through questionnaires was carried out by providing a google form containing statements to the parties related to the problem. To assess respondents' responses, the authors use a Likert scale that uses several question items to measure individual behavior by responding to 5 choice points on each question item. The analytical method used in this study is the Multiple Linear Regression analysis method with the application of IBM SPSS Statistics 25. The conclusion of this study shows that there is an influence of entrepreneurial behavior on consumer satisfaction at Gunung Sibayak Stores, Medan. The results showed that the t table value was t count 6.509 < t table 1.99601, so it can be concluded that H1 is accepted, which means that there is an influence of entrepreneurial behavior on consumer satisfaction at Gunung Sibayak Stores, Medan. The service of business actors has an effect on customer satisfaction at the Gunung Sibayak Store Medan. The results of the study obtained that the t table value was t arithmetic value 8.165 > t table 1.99601, so it can be concluded that H2 is accepted which means that there is an influence of business actor services on consumer satisfaction at Gunung Sibayak Store Medan